Electrocoagulation process for cobalt removal from industrial wastewater: Optimization and kinetic study - Ghanim S. Hassan; Ali H. Abbar (South African Journal of Chemical Engineering, 2025)
In the present work, the removal of cobalt from spent caustic wastes resulting from petroleum refining was studied using an electrocoagulation (EC) process with aluminum electrodes.. The influence of many factors such as pH, current density, and time on the performance of EC process was investigated and optimized using response surface methodology (RSM). The research outcomes showed that the current density has a remarkable effect on the removal efficiency. The optimal conditions were a current density of 15 mA/cm2, pH of 8, and a time of 40 min in which cobalt removal efficiency of 99 % was achieved with claiming an electrical energy consumption of 26.76 kWh/m3. It was observed that the decay of cobalt concentration verses time obeys first-order kinetics with a correlation coefficient (R2) of 0.999 and a rate constant of 0.112 min-1. Results showed that EC has the ability to remove not only the cobalt ions but also other contaminants causing a significant reduction in TOC, phenol, sulfide and turbidity which confirms the feasibility of industrial application the EC to treat spent caustic wastewater discharged from petroleum refinery processes.